Digital tools for smallholders in Egypt: The launch of a new price monitoring tool - Mahsoly - Abdelaziz, Fatma; Tarek, Abdallah (International Food Policy Research Institute, 2024)
The rapid adoption of mobile phones in agricultural and production systems provides an avenue to unlock the potential of digital innovations to transform smallholder agriculture in low- and middle-income countries. Previous research highlights how the adoption of digital tools can enhance farmers' profits and marketing outcomes by improving market efficiency through better supply and demand matching. Other research similarly emphasizes how digital innovations can facilitate agricultural transformation and transform the functioning of markets by addressing multiple forms of institutional and market failures. However, despite these advantages and the availability of numerous digital tools for agriculture, their adoption remains low and uneven across Africa, where agricultural markets are still underdeveloped. Smallholder farmers in developing countries, including Egypt, face challenges in accessing essential information, which limits their ability to leverage market opportunities and maximize profitability. Given the limited understanding of the primary challenges hindering Egyptian farmers' adoption of digital technologies and the strategies needed to enhance their access to these innovations, this paper aims to utilize an extensive survey of smallholder farmers in Egypt to: (i) examine the constraints to adoption of digital agricultural tools in Egypt; and (ii) assess the impact of farmer training programs on the awareness and adoption of digital tools, using the Mahsoly mobile application and its new price monitoring tool as a case study.